Structural and electronic properties of fulerol funcionalized with radiopharmaceuticals - Schopf, Patricia Ferreira; Silva, Ivana Zanella da; Martins, Mirkos Ortiz (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
The blood-brain barrier is one of the most difficult barriers to permeate of the organism, allowing only the passage of nutrients necessary for brain function. However, nanostructures, such as fullerol, have gained prominence by being able to cross this barrier. In parallel, fluorescent radiopharmaceuticals have been used in the diagnosis of different diseases that affect the central nervous system, also having affinity with one of the biomarker proteins of Azheimer’s disease: the phosphorylated tau protein. In an unprecedented, this work aimed to verify the electronic and structural properties of functionalized fullerol with different radiopharmaceuticals via ab initio computational simulation, in order to use this system as a marker for Alzheimer’s disease. The results demonstrated that the complexes formed a chemical bond without changing the properties of the isolated structures. Therefore, those systems can be considered stable for the intended application.